STUDI PERBANDINGAN KLAIM ATAS PEKERJAAN TAMBAH KURANG PADA FIDIC SILVER BOOK 2017 DAN HUKUM POSITIF DI INDONESIA - Denisa Sugih Ayu; Isis Ikhwansyah; Purnama Trisnamansyah (Gapenas Publisher, 2023)
Contractors and Employers often experience additional or reduced work, especially on EPC Projects due to the complexity of the project. Based on this, the Contractor or Employer submits a claim for the addition or revocation of the work. In practice, Contractors often experience misery related to work together with the actions of dominant Employers because there are no rules in positive law in Indonesia. This raises signs of non-compliance which is reflected in practice with the FIDIC Silver Book 2017 guidelines. This study aims to see the conformity of the implementation of verbal added-less claims on the EPC Project with the construction contract requirements in the FIDIC Silver Book 2017 with Law Number 2 of 2017 concerning Construction Services jo. Presidential Regulation Number 16 of 2018 concerning Procurement of Government Goods/Services, as well as knowing the form of legal protection for Contractors in the event of claims for work overload at the EPC Project by linking Indonesia's Positive Law with the FIDIC Silver Book 2017. This study uses a research method that has a normative legal approach and a comparative legal approach to construction claim settlement agreements. The specification of the research is descriptive analysis by providing a detailed and systematic description. Based on the research results, it can be concluded two things. First, in the terms of the FIDIC Silver Book 2017 construction contract, claims for additional work must be made in writing and are not permitted in oral form, while Law Number 2 of 2017 concerning Construction Services jo. Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services does not stipulate additional or less verbal job requirements. Second, actions that can be taken to provide legal protection to Contractors listed in Article 20 of the FIDIC Silver Book 2017 which expressly provides for a claim process for additional or less work if the Contractors in this case has the right to an extension of time, settlement or additional payment, submitted within a maximum period of 28 days, whereas in Law Number 2 of 2017 concerning Construction Services jo. Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services does not provide a clear form of legal protection for Contractors